Engaging Generation Z: Marketing Innovations in Islamic Boarding Schools for Sustainability - Aimah, Siti; Nasih, Muhammad; Wafiroh, Nihayatul; Fakhruddin, Fathiyah Mohd (JURNAL AL-TANZIM, 2024)
This study aims to analyze the strategy of Islamic boarding schools in marketing education amidst the onslaught of educational competition that utilizes digital technology by non-Islamic boarding school educational institutions and to find the unique marketing values of Islamic boarding schools that have made them survive until now. The approach used is qualitative with a case study type. Data collection is done through interviews, observations, and documentation. The analysis uses three interactive models: reduction, presentation, data depiction, and conclusion. The study results show that educational marketing is done by dominating social media, sharing information, activities, and achievements, and holding online registration. In addition, digital marketing is also carried out by managing websites and social media. These findings indicate that implementing a curriculum that focuses on students’ competence can be a model of adaptation for other Islamic boarding schools and influence educational marketing trends by directing strategies toward digital, increasing competitiveness, and preparing students to face future challenges. This Islamic boarding school also carries out digital content relevance in the form of graphic design training activities, applications, and creative videos and films.